Quantification of Respiratory and Muscular Perceived Exertions as Perceived Measures of Internal Loads During Domestic and Overseas Training Camps in Elite Futsal Players - Lu, Yu-Xian; Clemente, Filipe M.; Bezerra, Pedro; Crowley-McHattan, Zachary J.; Cheng, Shih-Chung; Chien, Chia-Hua; Kuo, Cheng-Deng; Chen, Yung-Sheng (Frontiers in Psychology, 2022)
Background: The rating of perceived exertion (RPE) scales with respiratory and muscular illustrations are recognized as simple and practical methods to understand individual psychometric characteristics in breathing and muscle exertion during exercise. However, the implementation of respiratory and muscular RPE to quantify training load in futsal training camps has not been examined. This study aimed to investigate respiratory and muscular RPE relationships during domestic (DTC) and overseas (OTC) training camps in an under-20 futsal national team. Methods: Data collected from eleven field players were used for comparison in this study (age = 18.7 ± 0.7 yrs, height =171.9 ± 6.1 cm, body weight = 64.2 ± 8.4 kg). All players reported Borg CR-10 RPE (RPECR10) and 7-scales respiratory RPE (RPErespiration) and muscular RPE (RPEmuscle) (Dalhousie pictorial scales) after training sessions and matches. Additionally, total distance (TD) and training impulse (TRIMP) were used to quantify external and internal loads via the Polar Team Pro system. Paired-sample t-tests were used to compare the RPECR10, RPErespiration, RPEmuscle, TD, and TRIMP between DTC and OTC. Furthermore, linear regression was performed to determine the relationships among all RPE scales,TD, and TRIMP. Results: The RPECR10 (p = 0.047), TD (p < 0.001), and TRIMP (p < 0.001) showed significant difference between DTC and OTC. Furthermore, linear regression analyses showed significant correlation between RPErespiration and RPEmuscle (DTC: r = 0.857, p= 0.006; OTC: r = 0.924, p < 0.001), RPECR10 and RPErespiration (DTC: r = 0.857, p= 0.001; OTC: r = 0.863, p= 0.001), and RPECR10 and RPEmuscle (DTC: r = 0.906, p < 0.001; OTC: r = 0.900, p < 0.001). Conclusion: Pictorial RPErespiration or RPEmuscle can be used as an alternative to quantify perceived measures of internal load during DTC and OTC in futsal players. Interpretation of perceived measures of training load and cardiac-related responses in association with external training load during short-term training camps would be useful in further understanding the demands of futsal players experience in these circumstances.